Digital Advertising Expenditures in the 2016 Presidential Election. (August 2018) - Williams, Christine B.; Gulati, Girish J. "Jeff"
Using 2012 and 2016 candidate disbursements and independent expenditures filing data collected by the Federal Election Commission, this study compares how much money both the presidential campaigns and outside groups spent on digital relative to traditional media. Digital campaign expenditures have increased their share of total media outlays markedly over recent election cycles, and in the 2016 presidential election, both the candidate and independent expenditures were higher than in 2012, particularly on the Republican side. This article investigates reasons for these trends and establishes a baseline for future research on the heretofore understudied topic of digital political advertising.